2022
DOI: 10.3389/fnut.2022.1066873
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of interactions between tripeptide NCW on cellular membrane using molecular dynamic simulation

Abstract: Tripeptide NCW identified in Mizuhopecten yessoensis has been shown to possess in vivo antihypertensive effect. However, the poor understanding of the absorption of NCW across the membrane limits its application. In this study, we have investigated the interaction of NCW with DPPC membrane via 400 ns all-atom molecular dynamic simulation using GROMACS software. The structural variations of NCW during absorption, the location and distribution of NCW in the membrane, and the effect of NCW on the properties of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…These peaks were satisfactorily fitted with Gaussian functions, as depicted in Figure b. This finding suggests that NCW induces phase separation of DPPC lipid bilayers, which aligns well with previous dynamics simulation results . Furthermore, the phase separation in DPPC liposomes may explain the decreased cooperativity of the phase transition …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These peaks were satisfactorily fitted with Gaussian functions, as depicted in Figure b. This finding suggests that NCW induces phase separation of DPPC lipid bilayers, which aligns well with previous dynamics simulation results . Furthermore, the phase separation in DPPC liposomes may explain the decreased cooperativity of the phase transition …”
Section: Resultsmentioning
confidence: 99%
“…However, the complex conditions of the gastrointestinal tract, including low pH and various digestive enzymes, as well as the intestinal epithelial barrier may cause premature degradation and hinder the penetration and absorption of these peptides, leading to limited oral bioavailability . In previous animal experiments involving serum and kidney metabolomics, as well as proteomics studies, it has been observed that the peptide Asn-Cys-Trp (NCW) derived from Mizuhopecten yessoensis, when administered at a dosage of 80 mg/kg BW, exhibits effective in vivo antihypertensive effects. However, considering the dosage of NCW used, it is necessary to enhance its bioavailability to achieve a better antihypertensive effect with a lower dose. According to the ExPASy tools (PeptideCutter, ), the peptide sequence NCW is predicted to have one chymotrypsin cleavage site with a cleavage probability of 5.4% and one pepsin (pH > 2) cleavage site.…”
Section: Introductionmentioning
confidence: 99%